Stenomastigus pseudofranzi sp. n., from South Africa (Staphylinidae, Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2012)
A new species of the endemic South African genus Stenomastigus Leleup (Staphylinidae, Scydmaeninae, Mastigini), S.pseudofranzi sp. n. is described. Because some morphological structures of the new species highly resemble those of S.franzi Leleup, description of the latter species is supplemented with previously unknown details of the aedeagus (includingthe copulatory piece). Habitus, aedeagi, modified fore legs of males and other diagnostic characters of both species are illustrated.